Study of Affective, Continuance and Normative Commitment of Entrepreneurs in the Development of MSMEs in the Culinary Sector - Tahir, Thamrin; Hasan, Muhammad; Tahir, Muhammad Ilyas Thamrin; Nurjannah; Arisah, Nur (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine and examine how the affective, continuance, and normative commitment of entrepreneurship in the development of MSMEs in the culinary sector. This research was conducted on micro, small and medium enterprises, precisely at the Mas Mud meatball stall located in Bontonompo sub-district, Gowa district. Qualitative research methods are used in this study. This study tries to provide a deeper understanding of the affective, continuance, and normative commitment of entrepreneurship in the development of SMEs. The study explores the important question of how the three components of commitment affect the development of MSMEs that are perceived differently by both owners and employees at the Mas Mud meatball stall. The findings of the study indicate that there is a contribution of affective, continuance, and normative commitment in their influence on entrepreneurs in developing their businesses. The encouragement of self-confidence in an entrepreneur makes him able and willing to change and develop all things and potential in his business